The temporal effect of platelet-rich plasma on pain and physical function in the treatment of knee osteoarthritis: systematic review and meta-analysis of randomized controlled trials. Issue 1 (December 2017) - Shen, Longxiang; Yuan, Ting; Chen, Shengbao; Xie, Xuetao; Zhang, Changqing
Abstract Background Quite a few randomized controlled trials (RCTs) investigating the efficacy of platelet-rich plasma (PRP) for treatment of knee osteoarthritis (OA) have been recently published. Therefore, an updated systematic review was performed to evaluate the temporal effect of PRP on knee pain and physical function. Methods Pubmed, Embase, Cochrane library, and Scopus were searched for human RCTs comparing the efficacy and/or safety of PRP infiltration with other intra-articular injections. A descriptive summary and quality assessment were performed for all the studies finally included for analysis. For studies reporting outcomes concerning Western Ontario and McMaster Universities Arthritis Index (WOMAC) or adverse events, a random-effects model was used for data synthesis. Results Fourteen RCTs comprising 1423 participants were included. The control included saline placebo, HA, ozone, and corticosteroids. The follow-up ranged from 12 weeks to 12 months. Risk of bias assessment showed that 4 studies were considered as moderate risk of bias and 10 as high risk of bias. Compared with control, PRP injections significantly reduced WOMAC pain subscores at 3, 6, and 12 months follow-up (p = 0.02, 0.004, <0.001, respectively); PRP significantly improved WOMAC physical function subscores at 3, 6, and 12 months (p = 0.002, 0.01, <0.001, respectively); PRP also significantly improved total WOMAC scores at 3, 6 and 12 months (allp < 0.001); nonetheless, PRP did not significantly increased the risk of post-injection adverse events (RR, 1.40 [95% CI, 0.80 to 2.45], I 2 = 59%, p = 0.24). Conclusions Intra-articular PRP injections probably are more efficacious in the treatment of knee OA in terms of pain relief and self-reported function improvement at 3, 6 and 12 months follow-up, compared with other injections, including saline placebo, HA, ozone, and corticosteroids. Review registration PROSPEROCRD42016045410 . Registered 8 August 2016.